China : Economic Reform and Macroeconomic Management - Szapary, Gyorgy; Blejer, Mario; Burton, David; Dunaway, Steven (Washington, D.C. : International Monetary Fund, 1991)
China encountered problems preserving economic stability while pursuing reforms aimed at increasing its economic flexibility and efficiency. This paper examines China's experience with market-oriented reforms since 1978, offering lessons for other centrally planned economies in the midst of transition to free markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet